Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let's say that a map $f: V \rightarrow W$ between finite-dimensional real vector spaces is convex-linear if $f(\lambda x + (1-\lambda)y) = \lambda f(x) + (1-\lambda)f(y)$ for all $\lambda \in [0,1]$.

Let's say that a map $f: V \rightarrow W$ between finite-dimensional real vector spaces is affine if $f(\lambda x + (1-\lambda)y) = \lambda f(x) + (1-\lambda)f(y)$ for all $\lambda \in \mathbb{R}$.

From the definition, it seems that the requirement of being convex-linear is weaker than the requirement of being affine. However, I can't think of an example of a map which is convex-linear but not affine, but I also can't prove that convex-linearity implies affinity.

Can someone show me an example of a convex-linear map which is not affine? Or tell me how to prove that every convex-linear map is affine? Or give me an appropriate reference?

EDIT: With the intuition of Qiaochu Yuan's comment in mind, I've come up with the following proof:

Claim: Every convex-linear map is affine.

Proof: Let $f$ be convex-linear. For $\lambda \in [0, 1]$, We have that $f(\lambda x + (1-\lambda) y) = \lambda f(x) + (1-\lambda) f(y)$. For $\lambda \notin [0,1]$, we can assume without loss of generality that $\lambda < 0$ (in the other case where $\lambda > 1$, we can interchange the role of $x$ and $y$). We can write \begin{align} f(y) = f\left( \underbrace{\frac{1}{1-\lambda}}_{\in [0,1]}(\lambda x + (1-\lambda) y) + \left( 1 - \frac{1}{1-\lambda} \right) x \right). \label{bla} \end{align} By the convex-linearity of $f$, this reduces to \begin{align} &f(y) = \frac{1}{1-\lambda} f(\lambda x + (1-\lambda) y) + \left( 1-\frac{1}{1-\lambda} \right) f(x) \end{align} which in turn can be reduced to \begin{align} f(\lambda x + (1-\lambda x)) = \lambda f(x) + (1-\lambda) f(y). \end{align}

share|cite|improve this question
The first condition says that $f$ preserves line segments and the second condition says that $f$ preserves lines. Can you see geometrically why these conditions should be equivalent? (Imagine taking longer and longer line segments.) – Qiaochu Yuan Dec 9 '11 at 3:49

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Browse other questions tagged or ask your own question.